2022
DOI: 10.1007/s10055-021-00622-2
|View full text |Cite
|
Sign up to set email alerts
|

Identifying physiological correlates of cybersickness using heartbeat-evoked potential analysis

Abstract: Many studies have consistently proven that repeatedly watching virtual reality (VR) content can reduce cybersickness. Moreover, the discomfort level decreases when the VR content includes an unusual orientation, such as an inverted scene. However, few studies have investigated the physiological changes during these experiences. The present study aimed to identify psychophysiological correlates, especially the neural processing, of cybersickness. Twenty participants experienced two types of VR orientation (upri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…It's noteworthy that the decrease in Delta power contrasts with previous research [4,21]. Conversely, the increase in Beta wave power aligns with anxiety-related patterns [39].…”
Section: Do Eeg Brainwaves Differ Between Most Sicknessinducing and T...mentioning
confidence: 50%
See 2 more Smart Citations
“…It's noteworthy that the decrease in Delta power contrasts with previous research [4,21]. Conversely, the increase in Beta wave power aligns with anxiety-related patterns [39].…”
Section: Do Eeg Brainwaves Differ Between Most Sicknessinducing and T...mentioning
confidence: 50%
“…It has been proposed as a potential indicator of a person's awareness of their internal bodily processes. Chang et al found that the magnitude of the HEP activity at the frontal area might reflect the level of arousal caused by cybersickness [5]. Park et al found a decrease of magnitude of HEP activity, and an increase in the Alpha power during cybersickness [36].…”
Section: Ecgmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach examines how the brain processes cardiovascular activity with millisecond accuracy and requires that both time series are time-locked, the heartbeats be marked with events in the EEG signals, and the heart signal removed. This approach is the most popular [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] .…”
Section: The Two Approaches For Jointly Analyzing These Signalsmentioning
confidence: 99%